The Impact of Curriculum Change on the Mathematics Achievement of Georgia Public School Students - Davis, Pennie Star (My University, 2017)
The purpose of this study was to examine the effects of the Mathematics Quality Core Curriculum (QCC) and the Mathematics Georgia Performance Standards (GPS) on high school student achievement as measured by the SAT and ACT. The State of Georgia redesigned the mathematics curriculum in order to show higher achievement in mathematics by increasing the rigor. One would assume overall SAT and ACT math scores should increase. The National Council of Teachers of Mathematics (NCTM) (2013) stated improvement will take commitment and patience that may not come for a number of years. This study explored the effectiveness of mathematics curriculum reform. The findings of the study have the potential to inform future revisions of the Mathematics Georgia Standards of Excellence (MGSE) or other Georgia Curricula. The study used an ex post facto design with quantitative methods. Quantitative data were calculated for each research question to determine significant differences between the QCC and GPS curriculum models. SAT and ACT mean scores were evaluated using a series of paired t tests providing a comparison between each model. Descriptive statistics were assessed to look at increases and decreases in the mean scores to identify minor and major differences. Overall, it was found that the changes in curriculum made no difference in the mathematics achievement of students in Georgia. However, a comparison of schools in Georgia suggested small schools experienced small increases in mathematics achievement while large Title I schools experienced slight decreases in mathematics achievement.
Chapter I: INTRODUCTION 1 | Statement of the Problem 3 | Theoretical Framework 4 | Purpose of the Study 6 | Overview of Methodology 7 | Research Question 8 | Limitations 8 | Definition of Terms 9 | Chapter II: LITERATURE REVIEW 12 | Introduction 12 | Historical Overview of Mathematics Curriculum 12 | Quality Core Curriculum 13 | Georgia Performance Standards 14 | Learning Tasks for Georgia Performance Standards 16 | Mathematics Coaches 17 | Common Core Standards 17 | Challenges of New Curriculum 22 | National Trends in Curriculum Design 28 | Science, Technology, Engineering and Mathematics 28 | Science, Technology, Engineering and Mathematics vs. Science, Technology, Engineering, Art and Mathematics 30 | Science, Technology, Engineering and Mathematics vs. Science, Technology, Reading, Engineering, Art and Mathematics 31 | Algebra for All 32 | Graduation Requirements 33 | Scholastic Aptitude Test (SAT) 36 | American College Test (ACT) 37 | SAT and ACT Scores and College Success 40 | National Assessment of Educational Progress 41 | School Size 43 | School Size and Achievement 44 | Socioeconomic Status 47 | Social Economic Status and Achievement 49 | Summary 50 | Chapter III: METHODOLOGY 51 | Participants 51 | Ethical Considerations 54 | Instrumentation 54 | Design of the Study 55 | Data Analysis 56 | Summary 57 |
Keywords: Mathematics; Academic achievement; Education--Georgia; Curriculum change